Analysis of Monitoring and Evaluation System Development of Smoke-Free Area in Indonesia - Arief Hargono; Santi Martini; Kurnia Dwi Artanti; Rizma Dwi Nastiti; Muhammad Aziz Rahman (Faculty of Public Health, Hasanuddin University, Makassar, 2025)
The World Health Organization Bulletin data show that Indonesia's compliance score for non-smokers' protection efforts was 0.1 in 2016. This research aims to analyze the need for data, information, and indicators to support the implementation, monitoring and evaluation of Smoke Free Area (SFA) in Indonesia through system analysis. This is an operational research study using the Focus Group Discussion (FGD) and document methods. The research series at early stage in the development of an evaluation and monitoring system, utilizing a system develop-ment cycle approach. Data is collected by the SFA task force and the community based on system components. The results of this study show that the entity responsible for conducting the monitoring and evaluation of SFA is the Task Force and community. The new potential data and information that has not been existed in the previous system are community as the potential data source of monitoring SFA, strategic data for SFA including the existence of self-service machines for selling cigarettes, and socialization of SFA regulation, monitoring and evaluation as a strategic activity to improve the result of SFA regulation, institution status of SFA and changes in smoking behavior. The information generated by the monitoring and evaluation system includes the SFA status of the institutions which is used for decision making to support the SFA program and the tobacco control program. Continuous monitoring and evaluation are important to ensure policy effectiveness, identify components for improvement or expansion of policies, and increase stakeholder and public support to strengthen or develop SFA policies.